NMR as a new tool for cultural heritage application: The provenance of ancient white marbles. (10th January 2019) - Gutiérrez Garcia‐M., A.; Savin, M. C.; Cantin, N.; Boudoumi, S.; Lapuente, P.; Chapoulie, R.; Pianet, I.
Abstract : Identifying the origin of marble used in antiquity brings back to light details of the economic, social and political organization of classical societies, and characterizing in depth the chemistry of marble is key to discovering its provenance. Beyond X‐ray diffraction, which could reveal the presence of discriminant secondary crystalline phases and the quantification of accessory minerals combined with a multivariate analysis approach, solid‐state nuclear magnetic resonance (NMR) enables one to recognize the local structure arrangement of both crystalline and amorphous materials by looking at one or more selected atoms. In present paper targets the 13 C nuclide, and thus the major component of marble, calcium carbonate. Whatever their geological origin, marbles 13 C‐NMR spectra present only one resonance corresponding to the carboxyl function whose intensity and line width vary from one marble to another. If the variation of the NMR signal intensity observed is the result of great T1 variations (from 220 to 5300 s) and is linked to iron content, the line width reflects defects in the calcite crystal in which calcium has been replaced by another element such as magnesium, aluminium or strontium. The specific profile of the NMR signal has been used successfully to help determine the origin of some archaeological items.